Metabolic Fate of the Carboxyl Groups of Malate and Pyruvate and their Influence on δ13C of Leaf-Respired CO2 during Light Enhanced Dark Respiration - Lehmann, Marco M.; Wegener, Frederik; Barthel, Matti; Maurino, Veronica G.; Siegwolf, Rolf T. W.; Buchmann, Nina; Werner, Christiane; Werner, Roland A. (Frontiers in Plant Science, 2016)
The enhanced CO2 release of illuminated leaves transferred into darkness, termed “light enhanced dark respiration (LEDR)”, is often associated with an increase in the carbon isotope ratio of the respired CO2 (δ13CLEDR). The latter has been hypothesized to result from different respiratory substrates and decarboxylation reactions in various metabolic pathways, which are poorly understood so far. To provide a better insight into the underlying metabolic processes of δ13CLEDR, we fed position-specific 13C-labeled malate and pyruvate via the xylem stream to leaves of species with high and low δ13CLEDR values (Halimium halimifolium and Oxalis triangularis, respectively). During respective label application, we determined label-derived leaf 13CO2 respiration using laser spectroscopy and the 13C allocation to metabolic fractions during light–dark transitions. Our results clearly show that both carboxyl groups (C-1 and C-4 position) of malate similarly influence respiration and metabolic fractions in both species, indicating possible isotope randomization of the carboxyl groups of malate by the fumarase reaction. While C-2 position of pyruvate was only weakly respired, the species-specific difference in natural δ13CLEDR patterns were best reflected by the 13CO2 respiration patterns of the C-1 position of pyruvate. Furthermore, 13C label from malate and pyruvate were mainly allocated to amino and organic acid fractions in both species and only little to sugar and lipid fractions. In summary, our results suggest that respiration of both carboxyl groups of malate (via fumarase) by tricarboxylic acid cycle reactions or by NAD-malic enzyme influences δ13CLEDR. The latter supplies the pyruvate dehydrogenase reaction, which in turn determines natural δ13CLEDR pattern by releasing the C-1 position of pyruvate.